Diagnóstico dos procedimentos de manutenção predial nas edificações do Campus da Universidade Federal de Mato Grosso em Cuiabá - Araujo Neto, Paschoal Gavazza de (2015)
Managers usually is put aside by administrators, since interventions occurring at a time when a corrective action with high costs compared to the preventive action are required. Extending the useful life of materials and components of buildings could be achieved through preventive actions systematically conducted with the support of a building maintenance plan of the Campus buildings on UFMT in Cuiabá. The study identified the lack of a maintenance plan for the buildings. It collected database from the way maintenance actions carried out, promoted by UFMT, and analyzed it for the periods 2012-2014, when the demands for maintenance were recorded. This study was conducted considering the buildings subdivided into ten subsystems. As a result it was observed that the four subsystems with more demands were the frames subsystems, electrical installations, air conditioning and sanitary subsystem, with a total demand accounted of respectively 37,53%; 24,38%; 17,79% and 13,53%. Calculated the rate of demand for average construction time for building area during the study period, it was found that the newest buildings were those where there were proportionally the highest number of interventions unlike the old buildings where it would be expected most indications number of interventions. This result suggests that could have been deficiencies in the design and / or construction materials used and / or construction processes.